PENGEMBANGAN BAHAN AJAR TEMATIK BERBASIS MODEL DISCOVERY LEARNING SISWA KELAS V DI GUGUS V KECAMATAN KERAMBITAN KABUPATEN TABANAN - Desak Gede Twelva Wiryani; I Wayan Lasmawan; Ida Bagus Putrayasa (Universitas Pendidikan Ganesha, 2021)
This study aims to produce teaching materials in the form of teaching books based on Discovery Learning on the theme I Animal and Human Organ Movements, Sub-Theme I Animal Movement Organs. This research is a type of development research using the 4D model. The trial subjects in this study were expert subjects, namely media experts, material experts, and teachers in Cluster V, Kerambitan District, Tabanan Regency, as well as 42 students in grade V. The data collection technique was done by using a questionnaire. This questionnaire is used to assess textbooks developed in terms of material content and textbook appearance. Data were analyzed by descriptive quantitative and qualitative. The results of this study are seen from the validity is very feasible with an average value of 4.25, seen from the practicality is very practical with an average score of 89 teachers and an average value of students 82.75 and seen from the effectiveness, it is at a moderate level of effectiveness. with an average value of 0.60